NSAIDs and PPIs - review of new reports - Jakub Klas; Natalia Kluz; Klaudia Piwowar (Kazimierz Wielki University, 2021)
The aim of this study is to systematise knowledge on non-steroidal anti-inflammatory drugs (NSAIDs) - cyclooxygenase (COX) enzyme inhibitors and proton pump inhibitors (PPIs) inhibiting potassium hydrogen ATPase. A review of recent reports on possible side effects and new therapeutic options will be presented. Results: Over the last few years, reports of PPI side effects have been published: drug-induced thrombocytopenia, severe hypomagnesemia, hyponatremia or rhabdomyolysis. In the case of NSAIDs, ancillary therapeutic effects in the supportive therapy of multiple myeloma or in the reduction of adenoma formation in the colon stand out, but also cases of acute kidney injury in children. On the basis of meta-analyses, attempts were made to demonstrate the effect of individual NSAIDs on the occurrence of cardiovascular complications, stroke or myocardial infarction Conclusions: Despite the fact that the indicated preparations were admitted to the list of drugs several decades ago, still their pharmacological potential (on the example of NSAIDs, which can be successfully used even in complementary therapy) has not been fully exploited. The aforementioned reports on side effects must not be forgotten. It is possible that the examples presented in the review will raise awareness in order to use these drugs with greater respect, in accordance with the recommendations in the leaflet.